Sitagliptin After Ischemic Stroke in Type 2 Diabetic Patients. Issue 28 (July 2015) - Chen, Dong-Yi; Wang, Szu-Heng; Mao, Chun-Tai; Tsai, Ming-Lung; Lin, Yu-Sheng; Su, Feng-Chieh; Chou, Chung-Chuan; Wen, Ming-Shien; Wang, Chun-Chieh; Hsieh, I-Chang; Hung, Kuo-Chun; Cherng, Wen-Jin; et al.
<x xml:space="preserve">Abstract</x> Abstract The cerebrovascular safety and efficacy of sitagliptin, a dipeptidyl peptidase-4 inhibitor, in patients with type 2 diabetes mellitus (T2DM) with ischemic stroke remains uncertain. The aim of this study was to assess the efficacy and safety of sitagliptin in patients with T2DM with recent ischemic stroke. We analyzed data from the Taiwan National Health Insurance Research Database between March 1, 2009, and December 31, 2011. Ischemic stroke patients were identified from individuals with T2DM. Patients who received sitagliptin were compared with those who did not to evaluate the cardiovascular safety and efficacy of sitagliptin. The primary outcome was a composite of ischemic stroke, myocardial infarction, or cardiovascular death. A total of 5145 type 2 diabetic patients with ischemic stroke met our inclusion criteria and were followed for up to 2.83 years (mean, 1.17 years). Overall, 1715 patients (33.3%) received sitagliptin and 3430 patients (66.7%) did not. The primary composite outcome occurred in 190 patients in the sitagliptin group (11.1%) and in 370 patients in the comparison group (10.8%) (hazard ratio [HR] = 1.02; 95% confidence interval [CI], 0.85–1.21). Patients treated with sitagliptin had a similar risk of ischemic stroke, hemorrhagic stroke, and all-cause mortality with an HR of 0.95 (95% CI, 0.78–1.16, P = 0.612), 1.07 (95% CI, 0.55–2.11, P = 0.834), and 1.00 (95% CI, 0.82–1.22, P = 0.989), respectively, compared with patients not treated with sitagliptin. Treatment with sitagliptin in type 2 diabetic patients with recent ischemic stroke was not associated with increased or decreased risks of adverse cerebrovascular outcomes.